Magnetorheological Rotary Brake: Analysis, Design Considerations and Experimental Evaluation - Sapiński, Bogdan; Bydoń, Sławomir (Engineering Transactions, 2006)
The paper is concerned with analysis, design considerations, construction and experimental testing of a magnetorheological rotary brake (MR brake). Operation principle and basic relationships for the brake are discussed. Magnetic field distribution in the brake is numerically studied using the finite element method (FEM). Structure and materials used in the main components of the brake are described. The brake performance is evaluated via measurement of torque responses.